2016
DOI: 10.1186/s12885-016-2194-4
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative optical coherence tomography for assessing human lymph nodes for metastatic cancer

Abstract: BackgroundEvaluation of lymph node (LN) status is an important factor for detecting metastasis and thereby staging breast cancer. Currently utilized clinical techniques involve the surgical disruption and resection of lymphatic structure, whether nodes or axillary contents, for histological examination. While reasonably effective at detection of macrometastasis, the majority of the resected lymph nodes are histologically negative. Improvements need to be made to better detect micrometastasis, minimize or elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…Methods such as high-frequency ultrasound (HF-US) [13] and photoacoustic tomography (PAT) [14] have been investigated, reporting spatial resolutions of ~100 μm (HF-US) or ~50 μm (PAT); additionally, PAT has been used in conjunction with external contrast agents. To obtain improved spatial resolution without the need for labelling agents, optical modalities, such as optical coherence tomography (OCT), often described as the optical analog to ultrasonography, have been proposed [1522]. The detection of backscattered light, rather than sound, provides OCT with a spatial resolution of 1–20 μm, but only to a depth of 1–2 mm in turbid tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods such as high-frequency ultrasound (HF-US) [13] and photoacoustic tomography (PAT) [14] have been investigated, reporting spatial resolutions of ~100 μm (HF-US) or ~50 μm (PAT); additionally, PAT has been used in conjunction with external contrast agents. To obtain improved spatial resolution without the need for labelling agents, optical modalities, such as optical coherence tomography (OCT), often described as the optical analog to ultrasonography, have been proposed [1522]. The detection of backscattered light, rather than sound, provides OCT with a spatial resolution of 1–20 μm, but only to a depth of 1–2 mm in turbid tissue.…”
Section: Introductionmentioning
confidence: 99%
“…OCT has the potential to rapidly scan entire ex vivo lymph nodes intraoperatively, improving upon the sampling issues of intraoperative histopathology techniques. However, it is unclear if lymph node metastases can be adequately delineated based on endogenous optical scattering contrast alone [21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…A similar study, conducted with a commercial HHOCT device, suggested that intraoperative margin analysis in shave margin specimens could reduce reoperation rates at the cost of small increases in resected tissue volume [95]. The Boppart group has also advanced OCT for non-destructive detection of breast cancer metastasis in lymph nodes [196,197]. They proposed using OCT to examine the lymph node cortex in situ for metastatic disease, eliminating the need for lymph node dissection and the associated risk of lymphedema.…”
Section: Human Anterior Eye Surgerymentioning
confidence: 99%
“…They proposed using OCT to examine the lymph node cortex in situ for metastatic disease, eliminating the need for lymph node dissection and the associated risk of lymphedema. Their recent study in [197] demonstrated a mean sensitivity of 58.8% and specificity of 81.% for identifying reactive/metastatic lymph nodes. The detection sensitivity was complicated by image artifacts and limited depth penetration through tissue overlying the lymph nodes of interest.…”
Section: Human Anterior Eye Surgerymentioning
confidence: 99%
“…1), 52 as well as for imaging the surgical margins of resected tumor specimens 19,20,[53][54][55] and loco-regional lymph nodes in human breast cancer surgeries. 56 Related to OCT, optical coherence elastography provides 3-D maps of tissue mechanical properties, on the micrometer to millimeter scale. Here, a mechanical load is applied to tissue and the resultant displacement is measured using OCT.…”
Section: Other Label-free Optical Imaging Technologies For Assessing mentioning
confidence: 99%